Identification of Abietane-Type Diterpenoids and Phenolic Acids Biosynthesis Genes in Salvia apiana Jepson Through Full-Length Transcriptomic and Metabolomic Profiling - Hu, Jiadong; Wang, Feiyan; Liang, Fengying; Wu, Ziding; Jiang, Rui; Li, Jinxing; Chen, Junfeng; Qiu, Shi; Wang, Jing; Zhang, Yuchen; Li, Qing; Chen, Wansheng (Frontiers in Plant Science, 2022)
Salvia apiana (S. apiana) Jepson is a medicinal plant that is frequently used by the Chumash Indians in southern California as a diaphoretic, calmative, diuretic, or antimicrobial agent. Abietane-type diterpenoids (ATDs) and phenolic acids (PAs) are the main bioactive ingredients in S. apiana. However, few studies have looked into the biosynthesis of ATDs and PAs in S. apiana. In this study, using metabolic profiling focused on the ATDs and PAs in the roots and leaves of S. apiana, we found a distinctive metabolic feature with all-around accumulation of ATDs, but absence of salvianolic acid B. To identify the candidate genes involved in these biosynthesis pathways, full-length transcriptome was performed by PacBio single-molecule real-time (SMRT) sequencing. A total of 50 and 40 unigenes were predicted to be involved in ATDs and PAs biosynthesis, respectively. Further transcriptional profile using Illumina HiSeq sequencing showed that the transcriptional variations of these pathways were consistent with the accumulation patterns of corresponding metabolites. A plant kingdom-wide phylogenetic analysis of cytochromes (CYPs) identified two CYP76AK and two CYP76AH subfamily genes that might contribute for the specific ATDs biosynthesis in S. apiana. We also noticed that the clade VII laccase gene family was significantly expanded in Salvia miltiorrhiza compared with that of S. apiana, indicating their involvements in the formation of salvianolic acid B. In conclusion, our results will enable the further understanding of ATDs and PAs biosynthesis in S. apiana and Salvia genus.